Diversity of Arbuscular Mycorrhizal fungi in Ulu Sat forest reserve of Machang District, Kelantan - Norhafizah Md. Zain; Chuah Tse Seng; Mazira Che Mat; Saiful Azman Abdul Rahim (American-Eurasian Network For Scientific Information (AENSI) Publisher, 2016)
Bakground: Arbuscular Mycorrhizal (AM) fungi play crucial role in terrestrial symbiosis and one of the important components in soil microbial community. However, little is known about how soil AM fungal community varies in relation to soil properties in Kelantan. Objective: Therefore, the present study investigated the types and diversity of AM fungi and proper nutrient composition in soil under trees in native forest of Ulu Sat Forest Reserve of Machang, Kelantan. Methods: A total of 60 rhizosphere soil samples were collected from study sites. Then, the rhizospheric soil microfungus was studied using wet-sieving and decanting technique. Findings/results: Based on morphological characteristics, 26 AM fungi species were recorded, representing five genera, viz. Acaulospora (6 species), Glomus (14 species), Scutellospora (4 species). Gigaspora (1 species), Sclerocystis (1 species). Glomus was dominant genus in this study site. The AM fungi spore density ranged from 675 to 3020 per 100 g dry soil (average = 1945) and their species richness ranged from 2-9 (average = 5.20). Shannon–Wiener index was calculated to evaluate the AM fungal diversity and the values of species richness (S) and evenness (E) showed a positive correlation with the value of the biodiversity Index. Conclusion: The results of this study suggest that the soil physico-chemical properties can have a significant effect on fungal population and diversity. Although tropical rainforests support a high diversity of plants, their associated symbiotic fungi are not as diverse as we had expected, possibly because AM fungi are not specific to their host plant.